The Influence of Classic Music Therapy on Learning Concentration in School-Age Children - Aura Lailatul Febriani Krisvianti Putri; Widiharti Widiharti; Diah Fauzia Zuhroh; Diah Jerita Eka Sari (Fundamental and Management Nursing Journal, 2025)
Introduction: School-aged children are in the developmental stage of concrete operational thinking, where they begin to think logically and solve problems in a structured way. However, many children at this stage still experience difficulties in subjects which often requires high levels of concentration and problem-solving skills. This study aims to determine the effect of classical music therapy on learning concentration in school-aged children. Methods: This study employed a quasi-experimental design with a non-equivalent control group design. Population consisted of 42 school-aged children, a sample of 38 was obtained using a non-probability sampling. Classical music therapy was used as the independent variable, while learning concentration served as the dependent variable. Learning concentration was measured before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test to determine the effect intervention. Results: The results of the Wilcoxon statistical test yielded a ρ value of 0.00, which is smaller than the predetermined significance level (α = 0.05). This finding indicates that classical music therapy has a statistically significant effect on improving learning concentration in school-aged children. The outcome supports the notion that classical music stimulates cognitive, focus, and learning atmosphere. Conclusions: This study concludes that classical music therapy has a significant positive influence on learning concentration. The intervention was shown to enhance students’ ability to maintain focus and sustain attention during learning activities, suggesting that classical music supports environment for academic engagement. Results reinforce the importance of innovative educational interventions that address cognitive, emotional, and environmental factors in the learning process.